PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA SEKOLAH DASAR - Vina Irmawati (Jurnal Administrasi Pendidikan, 2022)
This research was conducted based on learning problems that teachers do more focus on cognitive abilities by using learning lessons in elementary schools, so that the learning method does not foster student activity. The method used in this research is Quasi Experimental Design, that has two classes or groups, the control and the experimental group which each group was conducted with 18 people. The subjects in this research were fourth grade students at SDN Parung, using a written test for the data collection technique. The results showed that there was an influence from the implementation of the discovery learning model on the mathematical reasoning abilities of elementary school students. This can be proven based on the results of the analysis of hypothesis testing obtained tcount-34.4713 ttable2.032245 and an increase in the mathematical reasoning ability of elementary school students it can be proven based on an average N-Gain of 0.88 which is in the high criteria. So the discovery learning model is the right way that is expected for teachers in helping students convey their ideas and ideas, as well as improving mathematical abilities, because this learning is a learning that educates students.